Enhanced adhesion between PEEK and stainless-steel mesh in resistance welding of CF/PEEK composites by various surface treatments. (October 2021) - Li, Xuekuan; Sun, Mingchen; Song, Jiupeng; Zhang, Tong; Zhao, Yan; Wang, Kai
In order to improve the interfacial adhesion of stainless-steel mesh reinforced poly(ether-ether-ketone) (SSM/PEEK) heating elements (HEs) used in the resistance welding process for continuous carbon fiber reinforced PEEK composites (CF/PEEK composites), three kinds of surface treatments, sandblasting, aryl diazonium grafting and silane grafting, were adopted on SSM surfaces. The functional groups were grafted successfully according to the Fourier Transform Infrared (FTIR) results and Energy Dispersive Spectrometer (EDS) results, and the surface morphologies of SSM changed significantly after different treatments. Although the tensile performances of sandblasted stainless-steel (SS) wire and sandblasted SSM were distinctly reduced, the lap shear strength (LSS) of joints with sandblasted SSM still slightly improved. Besides, the interfacial shear strength (IFSS) increased from 28 MPa for untreated SSM to 34 MPa for diazonium grafted SSM and 38 MPa for silane grafted SSM. Furthermore, the LSS results were in agreement with this trend, representing a 9% improvement for joints with diazonium grafted SSM and a 23% improvement for joints with silane grafted SSM compared with untreated CF/PEEK joints. After comparison, silane grafting was the most suitable surface modification for resistance-welded CF/PEEK joints. The interfacial bonding mechanism of CF/PEEK joints with silane grafted SSM was compared with that of untreated CF/PEEK joints, suggesting that the mechanical interlocking contributed to improved interfacial bonding.